Studies in Solid Solution Formation between Acetaminophen and Povidone and Mouth-dissolving Strip Formulation - Shahiwala, Aliasgar (Current Pharmaceutical Design, 2024)
Introduction: This invention reports the solubilization of Acetaminophen (ACM) within the Povidone (PVP K30) in the solid state for the first time. Methods: First-generation solid dispersions (SDs) were attempted with a different ratio of PVP K:30:ACM. SDs prepared were transparent, suggesting a solid solution (SS) formation, which was a serendipitous discovery. A minimum ratio of 1.25:1 PVP K30: ACM was required to form stable SS, suggesting discontinuous SS. A computational complex prediction tool, fourier transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC) confirmed the SS formation. Results: The oral strip formulation was developed from the PVP K30: ACM SS using Polyvinyl alcohol as a film-former found to be optimum concerning physicochemical properties, offering rapid drug dissolution and taste masking. Conclusion: The designed strip is suitable for delivering a child's dose (100-150 mg). However, the developed SS can be formulated as tablets, capsules, or oral dissolving tablets to deliver adult doses with improved therapeutic benefits and patient compliance.
Keywords: Solid dispersion